2013
DOI: 10.1088/0953-2048/26/5/055007
|View full text |Cite
|
Sign up to set email alerts
|

Degradation free epoxy impregnation of REBCO coils and cables

Abstract: In applications utilizing high-temperature superconductors (HTS) under high mechanical loads as high-field magnets or rotors of generators and motors, the rare-earth-barium-copper-oxide (REBCO) tapes have to be stabilized mechanically. This is achieved using support structures of structural materials and filling the voids in the support through the impregnation of the tapes. The impregnation prevents movement of the tapes and distributes mechanical loads evenly. With high mechanical strengths and low sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 14 publications
(21 reference statements)
0
45
0
Order By: Relevance
“…The readouts diverge as the strain gauge onto the free piece of REBCO tape follows the coated conductor's thermal expansion while the strain gauge on the sample is mainly influenced by the thermal expansion of the spring material. With −0.17 % at 4.2 K and −0.16 % at 77 K, the thermal expansion of the spring (Ti-6Al-4V) is very low, much lower than the coated conductors' thermal expansion [13]. The REBCO tapes samples are therefore strained in tensile direction.…”
Section: Determination Of Zero Strainmentioning
confidence: 99%
“…The readouts diverge as the strain gauge onto the free piece of REBCO tape follows the coated conductor's thermal expansion while the strain gauge on the sample is mainly influenced by the thermal expansion of the spring material. With −0.17 % at 4.2 K and −0.16 % at 77 K, the thermal expansion of the spring (Ti-6Al-4V) is very low, much lower than the coated conductors' thermal expansion [13]. The REBCO tapes samples are therefore strained in tensile direction.…”
Section: Determination Of Zero Strainmentioning
confidence: 99%
“…KIT proposed [94] a blend of araldite epoxy with quartz powder in a 1:1 ratio for degradation-free impregnated RE123 tapes/coils, targeted to Roebel cables. The blend is not the best match with RE123 conductors in terms of thermal contraction from RT to 77 K nor has its effectiveness against delamination been demonstrated with full-scale coils.…”
Section: Coil Impregnationmentioning
confidence: 99%
“…However, transverse/radial tensile stress due to cool down and centrifugal forces during operation are of greater concern. With regard to coil applications, critical current, I c , degradation of epoxy impregnated SC coils made of CC tapes adapting different deposition processes and different width has been reported elsewhere [5]- [7]. The I c degradation was associated with the characteristic delamination of the CC tape having a multilayer structure.…”
mentioning
confidence: 84%
“…It may occur mainly due to the coefficient of thermal expansion (CTE) mismatch among its constituent layers during cool down to its operating temperature [6]. On the other hand, other research group demonstrated that the I c degradation in SC coils cannot be solely attributed to the CTE difference; incompatibility between the impregnating material such as pure epoxy-resin and the SC film can also induce negative effect when both in contact [7]. Delamination of CC tapes can be further mitigated by thermal cycling [6], [8].…”
mentioning
confidence: 99%